Ta’līm al-Lughah al-’Arobiyyāh bi Istīkhdam al-Jarōid Litanmiyati Mahāroh al-Qiro’ah Fīy Madrosah Al-Kholīlahا BiJakārta al-Syarqiyyah - Baharun , Segaf; Ubaidillah (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
The background in this thesis is learning Arabic by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta. The main purpose of this learning is so that students are able to understand the basic rules of the Arabic language systematically, as well as understand and have the ability to read Arabic texts in accordance with the rules that have been set. Therefore, the researcher wants to study Arabic learning by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta, related to planning, implementation, problems, and solutions. The focus of this research are: 1) How to plan the use of learning Arabic by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta?, 2) How to apply the use of learning Arabic by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta ?, This study uses a qualitative approach and a descriptive design. Methods of collecting data through participant observation, in-depth interviews, and documentation. Data analysis techniques through reduction, exposure, and verification as well as drawing conclusions. Checking the validity of the data by using the extension of the study, persistence of observations, and triangulation of sources. The results of this study indicate that: 1) Planning the use of learning Arabic by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta includes: (a) determining learning themes, (b) learning objectives, (c) learning methods, (d) learning media, and (e) learning evaluation. 2) The application of the use of learning Arabic by using magazines to improve reading skills at Madrasah Kholilah, East Jakarta, among others: (a) The teacher starts by repeating the discussion theme, (b) The teacher reads the material in the magazine, and students write the meaning and meaning, ( c) the teacher explains it, (d) the teacher gives an appropriate example, (e) the teacher gives the students time to ask questions, (f) the teacher asks the students to memorize the terms in the magazine.